Chemical characterization and antinflammatory activity of the methanolic extract of Pelargonium robertianum L., "Geranio", in Mus musculus - Ibáñez V., Lucy A. (2022)
The present investigation was done to evaluate lethal dose fifty (DL50) and effective dose average (DE50) of the antiinflammatory effect of a methanolic extract of the leaves of Pelargonium robertianum L."Geranio". To evaluate the DL50, 36 mice were used, divided in groups of 6 animals that received different doses of the methanolic extract by oral route using intragastric cannulae. Animals were observed during the first 24, 48 and 72 hours. The value of the DL50 was of 8,717.02 mg/kg by the Lichfield and Wilcoxon method. DE50 following Winter's Model (1970) and Sughisita et.al. was also performed. We observed that the methanolic extract presented an inhibitory effect of inflammation when compared to that of Diclofenac (62%) obtaining 26, 38 and 57% for the different doses assayed. The Average Effective Dose obtained was of 681,9577 by the method of Probits with ANOVA (p=0.0001,F=5240, R2=0.9979). From the extract with antiinflammatory activity, phenolic compounds and the flavonoids Rutin and Quercetin were isolated, both inhibitors of cyclooxygenase. These compounds were observed by HPLC and TLC respectively and also three alkaloids named GM1, GM2,GM3, were analyzed by means of IR, HPLC, RMNC13, RMNHI.